Flood Simulation Analysis of the Biliu River Basin Based on the MIKE Model - Qi Liu; Dianwu Wang; Yulong Zhang; Li Wang (Complexity)
The Biliu River is the largest river in Dalian. The occurrence of floods and droughts in this basin has extremely important impacts on local industry, agriculture, and urban development. For a long time, the annual distribution of precipitation in the Biliu River Basin is extremely uneven, the river runoff varies greatly from year to year and season to year, floods and droughts occur frequently, and serious soil erosion results in fragile ecological environment and severe shortage of water resources. In this paper, the spatial and temporal changes of rainfall and runoff in the Biliu River Basin are studied through the coupling of the MIKE 11 model and the MIKE SHE model. The hydrological changes in the Biliu River Basin are simulated. The coupled model is verified by monthly runoff data from 1996 to 2015, and the simulation values are found to be true. The values match well. Based on the cyclical pattern of precipitation and runoff in the Biliu River Basin, the rainfall and runoff data in the Biliu River Basin from 2016 to 2030 are derived. The MIKE SHE/MIKE 11 coupling model is used to predict the Biliu River from 2016 to 2030. The results show that flood disasters are expected to occur in August 2020, July 2025, and July 2030, which can provide a basis for hydrological management in the Biliu River Basin.